Inherently Chiral Macrocyclic Oligothiophenes: Easily Accessible Electrosensitive Cavities with Outstanding Enantioselection Performances. Issue 47 (10th October 2014) - Sannicolò, Francesco; Mussini, Patrizia R.; Benincori, Tiziana; Cirilli, Roberto; Abbate, Sergio; Arnaboldi, Serena; Casolo, Simone; Castiglioni, Ettore; Longhi, Giovanna; Martinazzo, Rocco; Panigati, Monica; Pappini, Marco; et al.
Abstract Invited for the cover of this issue is Francesco Sannicolò and co‐workers at different Italian institutions, who all contributed to the different specific areas of this multidisciplinary work. The image depicts inherently chiral elliptical and triangular oligothiophene macrocycles and their symmetrical resemblance to mysterious crop circles. Read the full text of the article at 10.1002/chem.201404331.